Renewable Methane from Ammonium Bicarbonate Supplemented Petrochemical Wastewater Treatment During Anaerobic Co-Digestion in CSTR - Siddique, Md. Nurul Islam; Zularisam, A. W. (Elsevier Ltd, 2012)
Scarcity of nitrogenous resource and buffering capability were recognized as reverting failure in earlier research treating petrochemical wastewater in anaerobic continuous stirred tank reactors. The purpose of this work is to explore the use of ammonium bicarbonate (NH 4 HCO 3 ) as supplementation ensuring nitrogenous supply and buffering requirement. With a view to measure the effect of NH 4 HCO 3 on the anaerobic process, a set of dosing up to 40mg/L was examined. The result was evaluated in terms of biogas yield. It was found that10mg/L dosing was the optimal dosing without affecting methanogenesis. Moreover, mathematical calculation explained that this optimum dosing can enhance biogas yield up to 27.77% compared to control PWW digestion. Results showed an obvious financial advantage to make the industrial application feasible.